Characteristics of the New Fiber Flax Variety HERA in Terms of Fiber Quality Parameters Regard to Agronomic Assessment and Seeds Quality - Marcin Praczyk; Anna Kicińska-Jakubowska; Barbara Romanowska; MD Masud Alam; Katarzyna Wielgusz; Joanna Banach (Journal of Natural Fibers)
The work deals characteristics of new flax Hera variety in terms of fiber quality with regard to agronomic assessment and seeds quality. The results of the analyzes were related to the reference varieties Nike, Sara and Modran grown in Poland in 2022 season. The study included evaluation of agrotechnical experiment, flax straw and fiber evaluation taking into account the morphology and surface as well cross section of flax fiber. Moreover, seeds quality assessment were conducted. Hera variety was characterized by the highest total (6.27 t/ha, 0.627 kg/m2) and straw yield (5.16 t/ha, 0.516 kg/m2). Straw of Hera variety was characterized by the best average total (78.5 cm) as well as average technical (66.5 cm) length and average diameter (1.43 mm). In addition, it has fiber to raw straw content (16.42%) at a level comparable to the reference varieties. The metrological analysis of the fiber showed that the Hera variety fiber can be a good raw material for production of yarns.